Data Mining in Customer Relationship Management The Case of a Major Logistic Company - Nekvapil, Viktor; Rauch, Jan, 1948-; Šimůnek, Milan, 1975-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2012)
The thesis addresses possibilities of deploying the open source data mining system LISp-Miner in the customer relationship management (CRM), specifically in the area of lead management. This is basically a process of finding information about potential customers, qualifying those customers according to their potential (future value), and turning the selected potential customers to real customers. The data used includes the records concerning the lead management of a major logistic company operating worldwide (the company wanted to stay in anonymity). The data is analysed using the LISp-Miner system which is an academic software developed at the Faculty of Informatics and Statistics at the University of Economics, Prague. The thesis also pays attention to the collaboration with the business experts of the company which provided the data. The principle aim of the thesis is to provide information contributing to the possible change of internal processes of the company. Further aims are to propose directions of the use of the LISp-Miner system when solving a similar data mining task, and propose a simple and understandable way how to present the results. The aims have been achieved by doing the analysis in compliance with the CRISP-DM Methodology. The asset of the thesis is the description of the whole project which includes the analysis of real data using the LISp-Miner system. Further result of the thesis is the description of the lead management domain. Finally, the thesis offers the instructions and recommendations for future similar projects. Section I outlines the LISp-Miner system and its procedures. Section II - A case study describes the process of analysing the data. Two cycles ("iterations") of the analysis were performed. The chapters devoted to the both iterations have been structured according to the phases of the CRISP-DM Methodology. Section III summarises the observations gained during the entire project.
Moreover, it gives recommendations and instructions for the application in case a similar project of the data analysis using the LISp-Miner system is designed.
Vedoucí práce: Jan Rauch
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: znalostní technologie [obor dipl. práce]; diplomové práce; master's theses